Two-Dimensional Time-Harmonic Elastography of the Human Liver and Spleen - Tzschatzsch, Heiko; Trong, Manh Nguyen; Scheuermann, Tobias; Ipek-Ugay, Selcan; Fischer, Thomas; Schultz, Michael; Braun, Jurgen; Sack, Ingolf (Ultrasound in Medicine and Biology, 2016)
Measurement of shear wave speed of the liver and spleen by elastography is an established diagnostic procedure for the detection of hepatic fibrosis, portal hypertension and esophageal varices. However, current elastography systems are limited by the size and penetration depth of elastographic windows. In this study, 2D time-harmonic elastography is proposed for generating full field-of-view shear wave speed maps in great depth. Two-dimensional time-harmonic elastography uses external harmonic stimulation at multiple frequencies to create compound shear wave speed maps. The method is tested in a phantom with soft and stiff inclusions and used for elastography of the liver and spleen in 13 asymptomatic volunteers. Each volunteer was scanned twice to determine the sensitivity of the method to physiologic variations: first, after 2 h of fasting, and a second time, 15 min after drinking 1 L of water. The wave speed maps of the phantom clearly identified the soft and stiff inclusions, yielding values that were consistent with those from magnetic resonance elastography. In vivo wave speed values were 1.49 ± 0.11 m/s for the liver and 2.03 ± 0.15 m/s for the spleen in a lower-frequency band centered at 40 Hz and 3.15 ± 0.30 m/s for the spleen in a higher-frequency band centered at 120 Hz. After water intake, wave speed values increased by 6% in the liver (p = 0.002) and decreased in the spleen by 4% (p = 0.021, low-frequency band) and 6% (p = 0.0002, high-frequency band), suggesting the high sensitivity of the method to altered blood flow and perfusion pressure. Two-dimensional time-harmonic elastography of the liver and spleen is a promising method for measuring tissue stiffness at different states of blood flow and perfusion in a large tissue window and at great penetration depth.
CRIS-Team Scopus Importer:2022-08-03
Keywords: 2D ultrasound elastography; Blood perfusion; Liver; Multifrequency vibration; Spleen; Time-harmonic elastography